2014
DOI: 10.1159/000371439
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of Matrine on Tumor Invasion in N-Butyl-N-(4-Hydroxybutyl)Nitrosamine-Induced Urinary Bladder Carcinogenesis

Abstract: Aims: This study was designed to investigate the mechanisms and suppressive effects of matrine on the development of urinary bladder cancers induced by N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN) in rats. Methods: Male Sprague-Dawley rats were given BBN (200 mg/rat) twice a week for a period of 8 weeks. Oral administration of matrine (50 and 100 mg/kg) was started 1 week before BBN exposure for 35 weeks. Half of each bladder was histopathologically analyzed and the remainder was extracted for protein analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The results demonstrated that matrine had potent antitumor activity in pituitary cancer cells. This was consistent with the results that matrine suppressed bladder tumor invasion in a rat model, which could be primarily mediated by regulating the expression of COX-2 and cPLA2 in the bladder (17). Furthermore, we explored the molecular mechanism of matrine in pituitary cancer cells by western blotting analysis.…”
Section: Discussionsupporting
confidence: 88%
“…The results demonstrated that matrine had potent antitumor activity in pituitary cancer cells. This was consistent with the results that matrine suppressed bladder tumor invasion in a rat model, which could be primarily mediated by regulating the expression of COX-2 and cPLA2 in the bladder (17). Furthermore, we explored the molecular mechanism of matrine in pituitary cancer cells by western blotting analysis.…”
Section: Discussionsupporting
confidence: 88%
“…It has been confirmed that matrine could suppress the proliferation of numerous cancer cells in vitro, such as lung cancer [ 6 ], gastric cancer [ 7 ], liver cancer [ 8 ], breast cancer [ 9 ] and bladder cancer [ 10 ] cells. However, the anti-cancer effect of matrine is too weak to be used in antineoplastic chemotherapy alone.…”
Section: Introductionmentioning
confidence: 99%
“…28 More interesting, in an animal model of bladder tumor, Gao et al pointed out that MAT could suppress bladder tumor invasion via regulation of the cyclooxygenase-2 (COX-2), and cytosolic recombinant phospholipase A2 (cPLA2). 29 MAT treatment induced the inhibition of cell proliferation and invasion of bladder cancer, which was mediated by the PI3K/AKT signaling pathway, in vitro. 14 At the same time, a research displayed that MAT restrained prostate carcinoma, which was another kind of carcinoma of the urinary system.…”
Section: Discussionmentioning
confidence: 97%